ANALISIS PENERAPAN SISTEM MANAJEMEN KESEHATAN DAN KESELAMATAN KERJA PADA PROYEK KONSTRUKSI PEMBANGUNAN GEDUNG THE HIMANA CONDOTEL - Ni Made Sintya Rani; Ni Putu Indah Yuliana (Fakultas Teknik, Universitas Wiraraja, 2020)
Occupational Safety and Health (OSH) is the important component of construction project. Rapid development is less balanced with Occupational safety and Health application. PP 50 of 2012 explain that Occupational safety and health management system (SMK3) is required to implemented for all industry and service. The Himana Condotel is the one of the building construction project with the high risk accident, than the author do the analysis of the level of implementation of SMK3. The analysis use descriptive observational method with sample subject from management side and worker side. The different test analysis that use Mann Whitney U test and the study literature of SMK3 as contain in PP no. 50 of 2012 to know the extent of SMK3 application from contractor in planned, implemented and examined SMK3 at the Himana Condotel project. The result from this study is the extent of SMK3 implementation at the Himana Condotel Project that is SMK3 planned with the average from management subject 90,94 ± 3,431 and from worker subject 87,53 ± 3,417 its appertain in the satisfactory level of application. SMK3 implementation with the average from management subject 82,38 ± 0,754 and from worker subject 81,90 ± 2,338 its appertain in the satisfactory level of application, and SMK3 examined with the average from management subject 99,87 ± 0,020 and from worker subject 95,76 ± 4,987 its appertain in the satisfactory level of application.